A comparison of the in vitro effects of three fibrinogen concentrates on clot strength in blood samples from cardiac surgery patients. Issue 10 (1st September 2021) - Stolt, Henrik; Shams Hakimi, Caroline; Singh, Sukhi; Jeppsson, Anders; Karlsson, Martin
Abstract: Background: Fibrinogen concentrate is used clinically to improve hemostasis in bleeding patients. We investigated and compared the efficacy of three commercially available fibrinogen concentrates to improve clot strength in blood samples from cardiac surgery patients. Objectives: Postoperative blood samples were collected from 23 cardiac surgery patients. Samples were each divided into four vials, each supplemented with 1.125 mg of fibrinogen of one of three fibrinogen concentrates (RiaSTAP ®, Fibryga ®, FibCLOT ® ), or placebo. The fibrinogen dose corresponded to 2.5 g per 70 kg of body weight. Clot strength after supplementation was assessed in duplicate with rotational thromboelastometry (ROTEM ® ) using FIBTEM maximum clot firmness, EXTEM clot formation time, and maximum clot firmness assays. Results: In vitro fibrinogen concentrate supplementation of the samples resulted in higher plasma fibrinogen concentrations and improved clot strength with all three concentrates. Supplementation with FibCLOT increased FIBTEM maximum clot firmness (+46% [25th–75th percentile 35–55] compared to placebo) significantly more than did supplementation with Fibryga (+26% [21–35]) and RiaSTAP (+29% [22–47], p  < .001). FibCLOT supplementation also shortened EXTEM clot formation time and increased EXTEM maximum clot firmness to a greater extent than did the other concentrates (both p  < .001). Conclusions: At the selected dose, FibCLOT was more effective than Fibryga and RiaSTAP in restoring clot strength in postoperative blood samples from cardiac surgery patients. These results may have implications for the choice of fibrinogen concentrate and dosing.